Decoding Gen-Z: The Impact of Social Networks on Their Decision-Making Mechanisms - Monageng, Thapelo; Mabina, Alton (COMPETITIVE: Journal of Education, 2025)
This research explores the influence of social media on the decision-making mechanisms of Generation Z, particularly in the context of political engagement and voting behavior. With social media platforms becoming increasingly central to how Gen-Z interacts with information, this study investigates the frequency and patterns of social media use among university students in Botswana, focusing on platforms like Facebook, Twitter, and TikTok. A mixed-methods approach, incorporating both surveys and interviews, was employed to gather data from 345 participants at the University of Botswana. Findings reveal that a significant proportion of Gen-Z students encounter political content regularly on social media, with Facebook being the most frequently used platform for political engagement. The study highlights the role of social media in shaping political opinions, with many respondents indicating that their voting decisions were influenced by online interactions and content. However, concerns about misinformation and the reliability of sources were prevalent. The results provide insights into how social media platforms are increasingly integrated into Gen-Z’s decision-making processes, offering valuable implications for educators, marketers, and policymakers in Botswana. This research contributes to understanding the broader impact of social media on youth engagement in the political sphere and lays the groundwork for further studies on digital influence in African contexts.